Improving the Microbial Production of Amino Acids: From Conventional Approaches to Recent Trends - Zhang, Guoqing; Ren, Xueni; Liang, Xiuhong; Wang, Yaqun; Feng, Dexin; Zhang, Yujun; Xian, Mo; Zou, Huibin (Biotechnology and bioprocess engineering, 2021)
Variable industrial strains have been applied in the fermentation of bulk amino acids. Strain discovery and evolution, process optimization are traditional approaches to improve the yield and efficiency of the bio-production process, hence to compete with chemical or enzymatic process in amino acids production. With the fast development of bioengineering and synthetic biology, the strains can be rationally engineered to achieve better performance and gain the capacity in the fermentation of broader range of amino acids, especially for value-added amino acids. This proposed review aims to summarize traditional and recent strains in the microbial production of amino acids, characterize their metabolic pathways and present potential objectives for rational evolution. In addition, this proposed review prospect the recent opportunities and challenges in the microbial production of value-added amino acids (rare amino acids, non-canonical amino acids, and unnatural amino acids).